#### Answer

$a = -2 $

#### Work Step by Step

$f(-1) = (-1)^{2}a + 4
\\f(-1) = 1(a^2)+4
\\f(-1)=a^2+4$
Since $f(-1) = 2$, then
$f(-1)=a^2+4
\\2 = a + 4
\\2-4=a
\\-2=a$

Published by
Pearson

ISBN 10:
0-32193-104-1

ISBN 13:
978-0-32193-104-7

$a = -2 $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.